edukasi Edukasi Gizi Pangan Tempe Sebagai Pemberian Makanan Tambahan Terhadap Perilaku Pencegahan Stunting - mukhlis; Titih Huriah (2024)
Stunting is a problem of acute nutritional intake caused by a lack of nutritional intake. One of the interventions to prevent stunting in toddlers is to provide highly nutritious local foods such as tempeh.To analyze the effect of nutrition education on local tempeh food as supplementary feeding (PMT) to toddlers on stunting prevention behavior in toddler mothers. The research design used was a quasi-experimental design, which was a research model using two groups, namely the control group and the experimental group. With the nonequivalent control group design model, the sampling technique used was purposive sampling, and the sample consisted of two groups, namely the intervention group (n = 17) and the control group (n = 17), where the experimental group and the control group were not randomly selected. The instruments used are questionnaires and media modules. Education was given four times, with the first meeting focusing on nutrition, the second on stunting and how to prevent it, the third on how to process Tempe and train in preparing daily menus using Tempe, and the fourth meeting evaluating family behavior in utilizing Tempe by giving knowledge questionnaires. attitude and behavior. Analysis was used to see differences in measurement results before and after the intervention was carried out using the Wilcoxon and Mann-Whitney tests. There were differences in the intervention group's knowledge, attitudes, and behavior toward respondents compared to the control group. The results of the study showed that there was an increase in the knowledge, attitudes, and behavior of the respondents after being given the tempeh local food nutrition education intervention as supplementary feeding (PMT) in preventing stunting.